Pengembangan Media Neraca Lengan untuk Memfasilitasi Kemampuan Berpikir Logis Anak Usia Dini - Lisdiani, Revi; Mulyana, Edi Hendri; Lidinillah, Dindin Abdul Muiz (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2021)
This research is motivated by the problems in the field regarding the limited availability of learning media in facilitating early childhood logical thinking skills, especially recognizing differences in objects based on the size of the object's weight. The importance of the ability to think logically from an early age to prepare children to live their daily lives is inseparable from logical thinking. The purpose of this study is to develop learning media to facilitate early childhood analytical thinking skills. The method used in this research is the development method with the Educational Design Research (EDR) model of the McKenney and Reeves model, which has three stages of research: analysis and exploration, design and construction, and evaluation and reflection. Data collection techniques used in this study were interviews, observation, questionnaires, and expert validation. The products that have been developed are then validated by media experts, material experts, and educational experts and then revised by researchers according to the validator's suggestions. Products that have been declared eligible to be tested based on the results of expert validation then tried twice on a limited basis on group B children in TK PGRI Karangmekar. The results of this study indicate that the developed media, namely balance scale media to facilitate early childhood logical thinking skills, is suitable for use in learning according to the results of expert validation, teacher responses, and student's ability to use balance scale media in learning in a limited trial.